Cotidiano rural, cultura popular e desenvolvimento local na arena televisiva: um estudo sobre o programa Globo Inverno da Rede Globo Nordeste - SILVA, Jademilson (2010)
This is a descriptive study that uses the method of content analysis with qualitative interpretation of data. We have analyzed the TV program Globo Inverno which has been released by Globo Nordeste, a Brazilian Channel of TV. The genre of the program is entertainment journalistic. We have analyzed the categories of communication: journalism, advertising, education and entertainment. The research has been guided by the following questions: From the perspective of Folkcommunication, how are popular culture and rural everyday showed in mass media? And how is the local culture presented in developing site? The categories of communication were theorized by theoretical elements from everyday life, popular culture and Folkcommunication. It was also based in speeches of social actors involved in the reportages.